Physiological parameters of professional football players in teams of various levels - Dragutin Stojmenović; Tamara Stojmenović (IP Iermakov S.S., 2023)
Background and study aim. Soccer is a demanding sport which, in addition to technical and motor characteristics, also requires exceptional functional abilities of athletes to play at a high level. The aim of this study: 1) To analyze the disparities in physiological parameters among professional soccer players in teams of varying levels. 2) To explore potential connections between team ranking positions and the physiological attributes of professional soccer players. Material and Methods. 91 professional soccer players who compete in Serbian Super league (age 24.14±5.15) were included in the study. Participants were classified into two groups. The first group consisted of players from teams that were ranked from third to sixth place at the end of 2021/2022 competitive season (n=49). The second group of participants consisted of the players of the teams that were ranked in the last two places at the end of the above-mentioned season (n=42). Maximal oxygen consumption (VO2max), as well as running speeds and heart rates at first and second ventilatory thresholds (VT1 and VT2) were obtained by performing maximal cardiopulmonary exercise test. Results. The results showed a statistically significant difference in terms of VO2max values, running speeds and heart rates at VT1 and VT2 when the top and bottom ranked teams were compared (p < 0.001). Conclusion. The results of the study imply that playing high-level soccer requires exceptional functional abilities, which go beyond technical and tactical characteristics. These exceptional abilities enable players to continuously perform at high intensities during the games in order to achieve top results. Coaches should be aware of the importance of high aerobic capacity for achieving top results, especially if the team consists of less talented players.